Analisa Perancangan Sistem Informasi Pelaporan Fasilitas Umum dan Informasi Pembuatan E-KTP Untuk Masyarakat - Mohammad Puji Hari Setiawan; Fajar Masya (LPPM Universitas Abdurrab, 2020)
Public facilities provided by the government are a tool for the community to carry out daily activities. From the start of pedestrians, roads, traffic lights to landfills. In addition to public facilities, information on making E-KTP is also very helpful for the community in finding information on making E-KTP to make it easier. If there is damage or misuse of the facility, a corrective action or a quick solution is needed so that it can be reused. With the ignorance of the government or the surrounding apparatus regarding the damage or misuse it can cause disruption of the activities that occur every day. With the web-based application that I call